Climate Change and Air Pollution: The Twin Threats to Children’s Health and Well-Being - Sriroshan Sritharan, Elijah (Medicine, Law & Society, 2025)
Environmental factors, such as air pollution and climate change, significantly contribute to the global burden of disease and are critical to understanding health disparities between countries, with low- and middle-income nations facing the highest environmental health burdens across various diseases and injuries. While health is universally acknowledged as both a fundamental human need and a basic human right, yet the harmful effects of unhealthy environments disproportionately impact children. Research indicates that pre- and post-natal exposures to environmental toxicants can disrupt brain and lung development, impairing their function. These health impacts are distributed unequally, with marginalised populations experiencing greater harm. The IPCC identifies fossil fuel combustion as the primary driver of climate change. Epidemiological studies further highlight the existing and future consequences of climate change, including its effects on infectious diseases, cardiovascular and pulmonary diseases, and mental well-being.